Process of Privatization: Internasional Intial Public Offering (IPO) of an Indonesian State-Owned Enterprise (SOE) - Kuntoro Magkusubroto (ITB, 2011)
This papaer describes process of privatization through Internasional initial publi offering (IPO) if an Indonesia State Owned Entreprice (SOE). The case referred to in this paper is PT Tambang Timah, an Indonesia Mining SOE, which previously suffered from fundamental change in the industry but was successfully turned around prior to its IPO. The discussion starts with the background on privatization of SOEs by highlingthng the historical policies of Government toward SOE's performance. It followed by a summary description of a successful turn-around and privatization of PT Tamabng Timah as the case example. It concluded with some lessons learned from the process as well as the specific case.